Wolffia columbiana (Araceae, Lemnoideae): first record of the smallest alien flowering plant in southern Europe and Italy. Issue 2 (3rd April 2017) - Ardenghi, Nicola M. G.; Armstrong, Wayne P.; Paganelli, Daniele
Abstract: Wolffia columbiana (Colombia watermeal), a naturalized American neophyte, is recorded for the first time from southern Europe. Identification, distribution, invasion status, ecology, and pathways of introduction are presented. Furthermore, the potential invasive behaviour and impacts in the new growing site have been assessed with the EPPO prioritization process scheme for invasive alien plants.